RANCANG BANGUN ALAT PEMANTAU PENGGUNAAN ENERGI LISTRIK RUMAH TANGGA BERBASIS INTERNET - Sri Suryaningsih; Sahrul Hidayat; Faisal Abid (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Electrical energy is a necessity for human beings and the use of electrical energy which is pretty much contained in the household sector. Electricity used in the household sector amounted to 35% of the total electricity consumed in Indonesia every month. The savings in energy use in the household are the first step that can be done to anticipate the energy crisis. The purpose of research makes a tool that can monitor and calculate the power consumption used by an electronic device or in whole in a home can be performed remotely using the internet in data transmission, in which the electrical power used is displayed on a PC screen in a WEB site. The results have been made hardware design, software, web design and manufacture. Results of testing done by looking at household electrical power are seen at the web address compared results observed directly shows good accuracy.Keywords: household, electrical power, distance, WEB.